Early Increases in Multiple Biomarkers Predict Subsequent Cardiotoxicity in Patients With Breast Cancer Treated With Doxorubicin, Taxanes, and Trastuzumab - Ky, Bonnie (J Am Coll Cardiol, 2013)
OBJECTIVES: The aim of this study was to determine if individual or multiple biomarkers are associated with cardiotoxicity in patients with breast cancer undergoing cancer therapy. BACKGROUND: Current methods to identify patients at risk for cardiotoxicity from cancer therapy are inadequate. METHODS: We measured 8 biomarkers in a multicenter cohort of 78 patients with breast cancer undergoing doxorubicin and trastuzumab therapy: ultrasensitive troponin I (TnI), high-sensitivity C-reactive protein (CRP), N-terminal pro–B-type natriuretic peptide (NT-proBNP), growth differentiation factor (GDF)-15, myeloperoxidase (MPO), placental growth factor (PlGF), soluble fms-like tyrosine kinase receptor (sFlt)-1, and galectin (gal)-3. Cardiotoxicity, defined by the Cardiac Review and Evaluation Committee criteria, was assessed every 3 months for up to 15 months. Hazard ratios (HRs) of cardiotoxicity risk were assessed for each biomarker at baseline, at visit 2 (3 months), and as a function of the difference between visit 2 and baseline. Joint models were assessed for the most promising biomarkers. RESULTS: TnI, CRP, GDF-15, MPO, PlGF, and sFlt-1 levels increased from baseline to visit 2 (p < 0.05). A greater risk of cardiotoxicity was associated with interval changes in TnI (HR: 1.38 per SD; 95% confidence interval: 1.05 to 1.81; p = 0.02) and MPO (HR: 1.34 per SD; 95% confidence interval: 1.00 to 1.80; p = 0.048) and in models combining both markers (p = 0.007 and p = 0.03, respectively). The risk of cardiotoxicity was 46.5% in patients with the largest changes in both markers (ΔTnI >121.8 μg/l; ΔMPO >422.6 pmol/l). CONCLUSIONS: Early increases in TnI and MPO levels offer additive information about the risk of cardiotoxicity in patients undergoing doxorubicin and trastuzumab therapy. Independent validation of these findings is necessary before application to clinical practice.